2015
DOI: 10.1016/j.molcel.2015.10.037
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-Dependent Phosphorylation of GAPDH Triggers Sirt1 Activation and Is Necessary for Autophagy upon Glucose Starvation

Abstract: Eukaryotes initiate autophagy to cope with the lack of external nutrients, which requires the activation of the nicotinamide adenine dinucleotide (NAD(+))-dependent deacetylase Sirtuin 1 (Sirt1). However, the mechanisms underlying the starvation-induced Sirt1 activation for autophagy initiation remain unclear. Here, we demonstrate that glyceraldehyde 3-phosphate dehydrogenase (GAPDH), a conventional glycolytic enzyme, is a critical mediator of AMP-activated protein kinase (AMPK)-driven Sirt1 activation. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
203
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(217 citation statements)
references
References 54 publications
13
203
1
Order By: Relevance
“…Previous studies have shown that during starvation, SIRT1 separates from the inhibitory molecule CCAR2/DBC1, and then gets activated by AMP-activated protein kinase (AMPK). 11,12 In the present study, BRD4 is found to form a complex with SIRT1 and CCAR2. Starvation can disrupt the SIRT1-CCAR2 interaction, whereas inhibition or silencing of AMPK does not.…”
Section: 10supporting
confidence: 53%
“…Previous studies have shown that during starvation, SIRT1 separates from the inhibitory molecule CCAR2/DBC1, and then gets activated by AMP-activated protein kinase (AMPK). 11,12 In the present study, BRD4 is found to form a complex with SIRT1 and CCAR2. Starvation can disrupt the SIRT1-CCAR2 interaction, whereas inhibition or silencing of AMPK does not.…”
Section: 10supporting
confidence: 53%
“…One potential regulatory mechanism following adrenergic stimulation is phosphorylation of GAPDH to increase activity (40,41). Studies have shown several kinases regulated by adrenergic stimulation; including Akt/PKB, CaMKIIβ, PKC, and AMPK, phosphorylate GAPDH to enhance activity (42)(43)(44)(45). Thus, the observed decrease in the ration of phosphorylated to total GAPDH protein in adrenergic-deficient embryos is consistent with the decreased enzymatic activity observed for GAPDH in these embryos.…”
Section: Glyceraldehyde-3-phosphatesupporting
confidence: 65%
“…The role of the PACS proteins in the nucleus is just beginning to be understood. Notably, PACS-2 is the most recent addition to a small collection of proteins that regulate SIRT1, which include deleted in breast cancer 1 (DBC1; also known as CCAR2), active regulator of SIRT1 (AROS; also known as RPS19BP1) and the moonlighting protein GAPDH (Kim et al, 2007(Kim et al, , 2008Atkins et al, 2014;Chang et al, 2015). It will be important to determine whether PACS-2 acts in the same or different pathways to the other SIRT1 regulators and whether PACS-2 or PACS-1 regulates HDACs in addition to SIRT1.…”
Section: Discussionmentioning
confidence: 99%